Lanxess expands production capacity for micronized red iron oxide pigments. Issue 12 (December 2018) - Unknown
Abstract : German speciality chemicals producer Lanxess reports that it continues to optimize its global production network for the manufacture of iron oxide pigments. The company has recently increased the production volume for its Bayferrox and Colortherm micronized red pigments by more than 5000 tonnes per year at its Krefeld-Uerdingen site in Germany through a targeted 'debottlenecking' process.